Isolated Right Ventricular Myocardial Infarction: An Orphan in Acute Coronary Syndrome Imaging - Sukhvinder Singh; Kamal Kumar Sethi (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2016)
Introduction: Isolated right ventricular myocardial infarction is an uncommon entity in the spectrum of acute coronary syndrome. It is often overlooked during the assessment of patients suspected to have acute coronary syndrome. Case Presentation: A 58 years old male presented with atypical chest discomfort. The initial ECGs were not supporting. The Echocardiogram revealed an isolated right ventricular myocardial wall motion abonrmality that was initially missed. Coronary angiogram revealed a co-dominant circulation with 100% occlusion of proximal right coronary artery. The distal right coronary artery was receiving collateral from left circulation. Successful angioplasty of right coronary artery was done with almost complete recovery of right ventricular function. Conclusion: The case emphasizes the importance of looking for isolated right ventricular infarction during echocardiography in all cases of suspected acute coronary syndrome.